Comunicare i fondi europei per promuovere lo sviluppo del territorio Una proposta operativa - Raspadori, Fabio (Diritto e società, 2021)
The volume is the result of a one-year project of research and fieldwork. It is the outcome of the "European funds - a Sustainable Future for Umbria" (ESFU) project, co-financed by the European Commission with the "Support for information measures relating to the EU Cohesion policy" program. Communicating European Union opportunities are essential for the effectiveness of cohesion policy, which aims to promote and support the overall harmonious development of its Member States and regions. However, it is a difficult task when the advantages that want to be reached are so clear. Among these, the contribution of regions and local authorities together with stakeholders, beneficiaries and citizens can increase the possibility of development. While the lack of knowledge can impact the performance of cohesion policy and undermine territory opportunities (local authorities, entrepreneurs, third sector and other actors), determining a low level of participation effectively affects the impact of European regional development and the social fund. The proposal elaborated in this book tries to fill this gap, elaborating a method to facilitate the state of communication strategy at the regional level. Thanks to an interdisciplinary approach that combines knowledge from different disciplinary fields from the legal framework to communication. The volume analyses the actual scenario of the structural fund's communication in the Umbria region to put forward a final proposal to establish a Network on regional European funds, called "REFORE". It should be a permanent mechanism for acquiring and disseminating information among potential recipients. The proposal thought for the Umbria context is replicable everywhere, shaping to a different environment.